2018
DOI: 10.1017/jfm.2018.770
|View full text |Cite
|
Sign up to set email alerts
|

Subgrid modelling for two-dimensional turbulence using neural networks

Abstract: In this investigation, a data-driven turbulence closure framework is introduced and deployed for the sub-grid modelling of Kraichnan turbulence. The novelty of the proposed method lies in the fact that snapshots from high-fidelity numerical data are used to inform artificial neural networks for predicting the turbulence source term through localized gridresolved information. In particular, our proposed methodology successfully establishes a map between inputs given by stencils of the vorticity and the streamfu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
255
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 267 publications
(256 citation statements)
references
References 54 publications
(44 reference statements)
1
255
0
Order By: Relevance
“…The CNN mapping, on the other hand, seems more suitable for applications where a large amount of training data is available in the form of snapshots. While intelligent SGS modeling frameworks can model true SGS stresses accurately, they are prone to numerically unstable prediction in the a posteriori deployment as shown in recent studies [37,52]. To exploit the potential of these black-box models in safety critical applications, we further investigate their robustness in predicting eddy viscosity coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CNN mapping, on the other hand, seems more suitable for applications where a large amount of training data is available in the form of snapshots. While intelligent SGS modeling frameworks can model true SGS stresses accurately, they are prone to numerically unstable prediction in the a posteriori deployment as shown in recent studies [37,52]. To exploit the potential of these black-box models in safety critical applications, we further investigate their robustness in predicting eddy viscosity coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…One more advantage of this approach is that numerical stability during the a posteriori deployment will be enforced. Maulik et al [37] noted that clipping of vorticity source term is required to attain the numerical stability during the deployment of data-driven SGS model. The similar observation was also found by Beck et al [52] for the decaying homogeneous isotropic turbulence problem.…”
Section: Intelligent Eddy Viscosity Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We can observe that SR approaches satisfactorily identify the value of the modelling constant c s , which controls reasonably well the right amount of dissipation needed to account for the unresolved small scales. We also highlight that several deep learning frameworks such as ANNs have been exploited for subgrid scale modelling for 2D Kraichnan turbulence [126][127][128] . The importance of feature selection can be seen in these works where different invariant kernels, like those listed in the feature library given in Eq.…”
Section: D Kraichnan Turbulencementioning
confidence: 99%
“…In the same way that numerical relativity simulations of BBH mergers have been critical for the detection and characterization of these sources with GW observations, numerical relativity simulations of BNS and NSBH mergers are critical to get insights into the physical processes that may lead to the production of electromagnetic and astro-particle counterparts, and to better interpret MMA observations 67 . These modeling efforts do not currently benefit from DL, but recent studies have suggested the possibility to improve the efficiency and robustness of simulations, enabling the inclusion of detailed microphysics [68][69][70][71][72] , and a significance increase in the speed with which partial different equations are solved 73,74 .…”
Section: Real-time Detection Of Gws and Neutrinosmentioning
confidence: 99%